Designing a holistic professional development program for elementary school english teachers in colombia (2007)
The design and implementation of a holistic professional development program for elementary school English teachers in Colombia concerns target language improvement and pedagogical reflection. School-based and learner-centered, the program is characteristic of a synthetic, progressive, process-oriented curriculum as teachers’ language and pedagogical needs determined the learning and pedagogical activities for the program. The teachers improved their use of conventional English and became aware of an alternative approach for early foreign language instruction. They reported increased confidence using English and implementing new methodological strategies by getting positive feedback from their learners. Positive changes in teachers’ and students’ attitudes towards English suggest that this holistic approach be used as a viable professional development program for elementary school teachers in Colombia. Key words: EFL teacher professional development, elementary school EFL teachers, program design, target language development, pedagogical reflection El diseño y la implementación de un programa holístico de desarrollo profesional para profesores de inglés de la básica primaria en Colombia está dirigido hacia el mejoramiento de la lengua extranjera y la reflexión pedagógica. El programa, situado en el contexto escolar y centrado en el docente como aprendiz, se caracteriza por ser sintético, progresivo y orientado hacia procesos debido a que las necesidades lingüísticas y pedagógicas de los profesores determinaron las actividades pedagógicas y de aprendizaje del programa. Los profesores mejoraron el uso del inglés convencional y adquirieron conciencia de un enfoque alternativo para la instrucción temprana en lengua extranjera. Informaron un aumento en su confianza para utilizar el inglés y para implementar nuevas estrategias metodológicas al recibir realimentación positiva de sus estudiantes. Los cambios positivos observados en las actitudes de los profesores y estudiantes hacia el inglés indican que este enfoque holístico puede constituirse en un programa de desarrollo profesional para profesores de básica primaria en Colombia. Palabras Clave: Desarrollo profesional de profesores de inglés como lengua extranjera, profesores de inglés de la básica primaria, diseño de programas, desarrollo de la lengua extranjera, reflexión pedagógica